(untitled) (Jurnal Teknodik, 2014)
Abstrak: Pendidikan berbasis karakter dan budaya sangat penting diberikan dalam proses pendidikan. Pemanfaatan TIK secara baik dan benar dapat digunakan untuk mendukung pelaksanaan pendidikan karakter yang menjadi cita-cita luhur pendidikan nasional. Dalam membangun karakter, proses pendidikan dan pembelajaran hendaknya diarahkan (diorientasikan) tidak hanya menjadi konsumen pengetahuan tetapi juga menjadi produsen sebuah pengetahuan. Untuk menjadi produsen pengetahuan, budaya membaca dan menulis harus dilatih melalui penggunaan TIK. Penggunaan TIK harus mampu mendorong peserta didik menjadi orang orang hebat, yang bisa menulis secara ilmiah dan sistematis. Hal ini harus dilakukan secara integrasi melalui pendidikan TIK berbasis karakter dan budaya. TIK harus digunakan untuk menumbuhkan dan mengembangkan karakter peserta didik agar mampu menghasilkan kreativitas dan produktifitas. Kata Kunci: TIK, Pendidikan Karakter Abstract: Education based on character dan culture is important in the educational process (Andrew J.Milson, Marvin W. Berkowits 2003). Ratna Megawangi (2010) in her research said that intellectual intelligent (verbal and logical-mathematical) only gave 20% contribution to the peopleâ€™s successfulness in the society, and the other 80% was determined by the peopleâ€™s emotional intelligent (character). Even though the use of ICT factually has certain negative effects, ICT becomes a very importance factor in improving the quality of human resource.Â The use of ICT with all its potential can support effectively the character education implementation which is our concern now. In building the character the learner should be oriented to not only a knowledge consumer but also a knowledge producer. To become a knowledge producer, the writing and reading culture can be cultivated through the right use of ICT. ICT must be able to push and make someone a great people who can write systematically. This effort should be integrally done through ICT education based on character and culture. ICT should be use to grow and develop learnersâ€™ character that enable them to become creative and productive. Key Word: ICT, Character Education